1990
DOI: 10.1177/0310057x9001800106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adrenaline, Fentanyl and Warming of Injectate on Shivering following Extradural Analgesia in Labour

Abstract: This prospective, controlled study was undertaken to determine whether addition of adrenaline or fentanyl to bupivacaine or warming of the injectate had any effect on the incidence of shivering following extradural analgesia in the labouring parturient. Eighty-four patients were sequentially allocated to four groups (control, warm injectate, extradural adrenaline and extraduralfentanyl). The adrenaline group had the highest incidence of shivering, the warm injectate and fentanyl groups the lowest. Extradural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 18 publications
(3 reference statements)
0
7
0
1
Order By: Relevance
“…This was to limit the large fall in temperature ofthe lignocaine solution with time. 4 The onset of sensory blockade was defined as loss of perianal sensation to pinprick with a 27 gauge short-bevel disposable needle. Assessments of sensory blockade were made after the caudal injection of the local anaesthetic solution at oneminute intervals until loss of perianal sensation to pinprick.…”
Section: Methodsmentioning
confidence: 99%
“…This was to limit the large fall in temperature ofthe lignocaine solution with time. 4 The onset of sensory blockade was defined as loss of perianal sensation to pinprick with a 27 gauge short-bevel disposable needle. Assessments of sensory blockade were made after the caudal injection of the local anaesthetic solution at oneminute intervals until loss of perianal sensation to pinprick.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that PAS could be prevented by warming skin-surface [6] and warming the administered fluid [7,8], but it is not a perfect way. Many drugs have been shown to be effective on prevention of PAS, such as opioids, α2-agonist, anticholinergic, CNS stimulant, corticosteroid [9], however, few of them were recommended for the prevention of PAS due to various side-effects.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al 21 did not find any difference in shivering between patients receiving epidural 1.5% lidocaine with epinephrine 1:200 000 (20 mL) at body or room temperature. In contrast, Shehabi et al 22 found that patients receiving warmed compared to room temperature epidural bupivacaine had a lower incidence of shivering. Furthermore, Walmsley et al 23 demonstrated that the administration of warmed epidural bupivacaine resulted in the cessation of active shivering.…”
Section: Discussionmentioning
confidence: 90%